Ignorance is not bliss: Statistical power is not probability of trial success. Issue 4 (23rd October 2015) - Zierhut, ML; Bycott, P; Gibbs, MA; Smith, BP; Vicini, P
Abstract : The purpose of this commentary is to place probability of trial success, or assurance, in the context of decision making in drug development, and to illustrate its properties in an intuitive manner for the readers of Clinical Pharmacology and Therapeutics . The hope is that this will stimulate a dialog on how assurance should be incorporated into a quantitative decision approach for clinical development and trial design that uses all available information.